Effect of Tillage Practices on Selected Engineering Properties of Cassava (Manihot esculenta) Tubers - Olufemi Adeyemi Adetola; Olawale John Olukunle; O. O. Olubanjo; A. P. Olalusi (Nigerian Journal of Technological Development, 2020)
The main objective of this study was to determine the influence of tillage practices on selected engineering properties of cassava tubers. Two field tests were conducted between May 2014 to April 2015 and May 2015 to April 2016. Eight tillage practices utilized for the experiment were coded as; Ploughing + Harrowing (A), Ploughing + Harrowing + Ridging (B), Manual Ridging (C), Minimum Tillage (D), Ploughing + Harrowing + Manual Digging to a depth of 30 cm + Sawdust of 10 cm depth set at the base (E), Ploughing + Harrowing + Ridging + Sawdust of 10 cm depth set at the base (F), Manual Ridging + Sawdust of 10 cm depth put at the base (G) and Manual Digging to a depth of 30 cm + Sawdust of 10 cm depth put at the base (H). TMS 0581 improved cassava variety and two fertilizer rates 622.50 kg/ha and control were used. Randomized Complete Block Design was used.   The experiment was 8x2x1 factorial combinations in split-split plot design with three replications. The effect of different treatments on selected engineering properties of cassava tubers were determined. The results showed that Ploughing + Harrowing (A) tillage practice was significantly different from other tillage practices and gave the most suitable selected engineering properties of  size 10.53±0.64c cm, surface area 371.15±45.53bc cm2, sphericity 39.26±1.74a cm, roundness 21.40±3.29ab , bulk mass 21.43h kg, coefficient of static friction 2.73±0.06abc, compressive strain at break of 2.16±0.03e mm/mm, compressive load at break of 11698.90±178.71f N, compressive stress at break of 2.72±0.04d MPa, energy at break of 191.62±2.93e J, modulus automatic of 1.89±0.031c MPa, followed by F, G, D, C, E, H and B tillage practices respectively. The study had provided some engineering properties for engineers to develop efficient agricultural machines for handling and processing of fresh cassava tubers.